Awareness and Political Participation of UIN Raden Fatah Palembang Students Regarding Money Politics in General Elections - Minako, Muchlis (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
Students represent a significant segment of new voters in General Election contests. As newcomers to the electorate, students must develop a thorough understanding of political awareness and participation in elections. This study aims to examine students' comprehension of political awareness and their engagement with money politics, as well as the impact of such practices on elections. Utilizing both qualitative and quantitative methods, data were collected through surveys and in-depth interviews with 30 students. The findings reveal diverse levels of political awareness, shaped by factors including education, information access, social environment, and political experience. While most students demonstrate a solid understanding of money politics and express negative attitudes towards it, some encounter moral dilemmas. Economic background, education, and political experience significantly affect their views on money politics. This practice also influences their political participation by diminishing trust in the political system and reducing their motivation to engage. These results underscore the necessity of enhancing political awareness and addressing money politics among students to fortify democratic processes.